Handling Of Perma NO. 2 OF 2012 In Cases Of Light Accepting Offences In The Jurisdiction Of The Rokan Hilir Police Region - Bambang Suhartono Margolang; Kusno Kusno; Ahmad Ansyari Siregar (CV. AFDIFAL MAJU BERKAH, 2025)
The method used in this study is normative legal research, namely research on problems by looking at the sources of applicable regulations related to the title of Handling of Perma No. 2 of 2012 in cases of minor receiving in the jurisdiction of the Rokan Hilir Police. In the Decision of the Rokan Hilir District Court No. 9 / Pid.C / 2023 / PN Rhl, the verdict states that the Defendant Rosa Mayheppi Sinurat alias Rosa above was legally and convincingly proven guilty of committing the crime of minor receiving; Sentencing the Defendant therefore to imprisonment for 14 (fourteen) days. In this case, the verdict handed down by the Panel of Judges against the Defendant was lower than the demands of the Public Prosecutor who had demanded for 1 month, this was due to the existence of mitigating factors for the defendant which were taken into consideration by the Panel of Judges in making the verdict. The author hopes that the Rokan Hilir Police will be consistent in pursuing the receiver of every minor theft crime, which is also one of the benchmarks for reducing crime itself.